The absorption and uptake of recombinant human follicle-stimulating hormone through vaginal subcutaneous injections - a pharmacokinetic study - Kuo Hsin-Chih; Hsu Chao-Chin; Hsu Chao-Tien; Gu Qing (BMC, 2009)
Abstract Background Follicle stimulating hormone (FSH) has been routinely used for ovulation induction. Because of rapid clearance of the hormone, FSH is commonly administered by daily intramuscular or subcutaneous injections in in-vitro fertilization (IVF). To reduce the number of visits to the clinic, an intermittent vaginal injection of rhFSH every 3 days employing the concepts of mesotherapy and uterine first-pass effect was invented and has successfully been applied in women receiving IVF treatment. This study was designed to monitor the pharmacokinetic pattern of rhFSH administered vaginally. Methods Twelve healthy women with regular ovulatory cycles were recruited. All volunteers received gonadotrophin-releasing hormone agonist to suppress pituitary function and were assigned to receive single dose recombinant human FSH (rhFSH, Puregon 300) either using conventional abdominal subcutaneous injection or vaginal subcutaneous injection in a randomized cross-over study. Serum samples were collected at pre- scheduled time intervals after injections of rhFSH to determine immunoreactive FSH levels. Pharmacokinetic parameters characterizing rate [maximal plasma concentrations (Cmax) and time of maximal plasma concentrations (tmax)] and extent [area under the plasma concentration-time curve (AUC) and clearance] of absorption of rhFSH were compared. Results Vaginal injection of rhFSH was well tolerated and no drug-related adverse reaction was noted. Our analysis revealed that tmax was significantly earlier (mean 6.67 versus 13.33 hours) and Cmax was significantly higher (mean 17.77 versus 13.96 IU/L) in vaginal versus abdominal injections. The AUC0-∞ was 1640 versus 1134 IU·hour/L in vaginal and abdominal injections, respectively. Smaller plasma elimination rate constant (0.011 versus 0.016 hour-1), longer mean residence time (106.58 versus 70.47 hours), and slower total body clearance (292.2 versus 400.1 mL/hour) were also found in vaginal injection. Conclusion The vaginal injection mode elicited a rapid and highly extended absorption of rhFSH injected compared to conventional abdominal injection. These data indicate that the rate and extent of FSH absorption from the injection site can vary depending on the route of the FSH administration.